Effect of fluoride toothpaste with nano-sized trimetaphosphate on enamel demineralization: An in vitro study - Danelon, Marcelle [UNESP]; Pessan, Juliano Pelim [UNESP]; Souza-Neto, Francisco Nunes; de Camargo, Emerson Rodrigues; Delbem, Alberto Carlos Botazzo [UNESP] (Elsevier, 2017)
Objective This study evaluated the effect of toothpastes containing 1100 ppm F associated or not with micrometric or nano-sized sodium trimetaphosphate (TMP) on enamel demineralization in vitro, using a pH cycling model. Design Bovine enamel blocks (4 mm × 4 mm, n = 96) were randomly allocated into eight groups (n = 12), according to the test toothpastes: Placebo (without fluoride or TMP); 1100 ppm F (1100F); 1100F plus micrometric TMP at concentrations of 1%, 3% or 6%; and 1100F plus nanosized TMP at 1%, 3% or 6%. Blocks were treated 2×/day with slurries of toothpastes and submitted to a pH cycling regimen for five days. Next, final surface hardness (SHf), integrated hardness loss (IHL), differential profile of integrated hardness loss (ΔIHL) and enamel fluoride (F) concentrations were determined. Data were analyzed by ANOVA and Student-Newman-Keuls’ test (p < 0.05). Results The use of 1100F/3%TMPnano led to SHf 30% higher (p < 0.001) and IHL ∼ 80% lower (p < 0.001) when compared to 1100F. This toothpaste also resulted in ∼64% reduction of mineral loss (ΔIHL) when compared to 1100F. Moreover, the addition of nano-sized TMP promoted increases in enamel F uptake of 90%, 160% and 100%, respectively for the concentrations of 1%, 3% and 6%, when compared to 1100F (p < 0.001). Conclusion The addition of nano-sized TMP at 3% to a conventional toothpaste significantly decreased enamel demineralization when compared to its counterparts without TMP or supplemented with micrometric TMP.
Keywords: Demineralization; Nano-sized; Phosphates; Toothpastes